Faktor-Faktor yang Mempengaruhi Kelelahan Kerja pada Pekerja Produksi PT. Rabanton Maju Joyo Abadi Banyuwangi - HARNANDA, VINONA ALVIO; ERNAWATI, MEIRINA (Universitas Hang Tuah, 2023)
Work weariness is a pattern that develops in a scenario and often happens when everyone who has acted is able to resume their actions. This study's goal was to ascertain the impact of repetitive labor and mental strain on worker tiredness at PT. Rabanton Maju Joyo Abadi Banyuwangi. This research uses a cross-sectional study design and is an observational analytical study. The sample size in the study was as many as 35 concrete production workers at PT. Rabanton Maju Joyo Abadi Banyuwangi. The variables studied are individual characteristics, mental workload and monotonous work. Data was obtained by distributing questionnaires and interviews to workers. The data is presented in tabular format, and Chi-Square statistical analysis is used to analyze it using non-parametric statistical tests. According to the study's findings, characteristics such as age (p = 0.040), mental effort (p = 0.027), and monotonous job (p = 0.036) showed a significant association with work tiredness, however factors such as working duration (p = 0.211) and nutritional state (p = 0.187) did not. Based on the findings of this research, it can be concluded that characteristics such as age, mental burden, and monotony have a significant association with job tiredness, however factors such as working conditions and nutritional status do not. It is better to have socialization about work fatigue during safety talk and medical check-ups regularly.